The microbiological diagnosis of tuberculous meningitis: results of Haydarpasa‐1 study. (3rd April 2014) - Erdem, H.; Ozturk‐Engin, D.; Elaldi, N.; Gulsun, S.; Sengoz, G.; Crisan, A.; Johansen, I. S.; Inan, A.; Nechifor, M.; Al‐Mahdawi, A.; Civljak, R.; Ozguler, M.; et al.
Abstract We aimed to provide data on the diagnosis of tuberculous meningitis (TBM) in this largest case series ever reported. The Haydarpasa‐1 study involved patients with microbiologically confirmed TBM in Albania, Croatia, Denmark, Egypt, France, Hungary, Iraq, Italy, Macedonia, Romania, Serbia, Slovenia, Syria and Turkey between 2000 and 2012. A positive culture, PCR or Ehrlich–Ziehl–Neelsen staining (EZNs) from the cerebrospinal fluid (CSF) was mandatory for inclusion of meningitis patients. A total of 506 TBM patients were included. The sensitivities of the tests were as follows: interferon‐γ release assay (Quantiferon TB gold in tube) 90.2%, automated culture systems (ACS) 81.8%, Löwenstein Jensen medium (L‐J) 72.7%, adenosine deaminase (ADA) 29.9% and EZNs 27.3%. CSF‐ACS was superior to CSF L‐J culture and CSF‐PCR (p <0.05 for both). Accordingly, CSF L‐J culture was superior to CSF‐PCR (p <0.05). Combination of L‐J and ACS was superior to using these tests alone (p <0.05). There were poor and inverse agreements between EZNs and L‐J culture (κ = −0.189); ACS and L‐J culture (κ = −0.172) (p <0.05 for both). Fair and inverse agreement was detected for CSF‐ADA and CSF‐PCR (κ = −0.299, p <0.05). Diagnostic accuracy of TBM was increased when both ACS and L‐J cultures were used together. Non‐culture tests contributed to TBM diagnosis to a degree. However, due to the delays in the diagnosis with any of the cultures, combined use of non‐culture tests appears to contribute early diagnosis. Hence, the diagnostic approach to TBM should be individualized according to the technical capacities of medical institutions particularly in those with poor resources.